Aanguilla olfactory epithelium transcriptome assembly - Churcher, Allison M.; Hubbard, Peter C.; Marques, João P.; Canário, Adelino V. M.; Huertas, Mar (Dryad Digital Repository, 2015)
This is the Trinity assembled olfactory epithelium transcriptome (Illiumna HiSeq 2000) for Anguilla anguilla.